A remarkable new species of Mythomantis Giglio-Tos, 1916 from northern Borneo, with notes on the systematics of Deroplatyinae Westwood, 1889 (Mantodea: Mantidae) - Schwarz, Christian J.; Helmkampf, Martin (Zootaxa, 2014)
A conspicuous new species of praying mantid, Mythomantis serrata sp. nov., from the Malaysian part of Borneo is described and illustrated. A key to the three known species of the genus Mythomantis and their known geographic distribution is provided. Several morphological characters, most notably those in the male genitals, suggest a close relationship between Mythomantis and the Southeast Asian genera Pseudempusa and Deroplatys. As a consequence, we propose to transfer Mythomantis from Angelinae to Deroplatyinae, and Pseudempusa from Miomantinae Rivetinini to Deroplatyinae, while removing Brancsikia from this subfamily.